New pediatric percentiles of liver enzyme serum levels (alanine aminotransferase, aspartate aminotransferase, γ‐glutamyltransferase): Effects of age, sex, body mass index, and pubertal stage. Issue 4 (16th May 2018) - Bussler, Sarah; Vogel, Mandy; Pietzner, Diana; Harms, Kristian; Buzek, Theresa; Penke, Melanie; Händel, Norman; Körner, Antje; Baumann, Ulrich; Kiess, Wieland; Flemming, Gunter
Abstract : The present study aims to clarify the effects of sex, age, body mass index (BMI), and puberty on transaminase serum levels in children and adolescents and to provide new age‐ and sex‐related percentiles for alanine aminotransferase (ALT), aspartate aminotransferase (AST), and γ‐glutamyltransferase (GGT). Venous blood and anthropometric data were collected from 4, 126 cases. Excluded were cases of participants with potential hepatotoxic medication, with evidence of potential illness at the time of blood sampling and non‐normal BMI (BMI <10th or >90th). The resulting data (N = 3, 131 cases) were used for the calculations of ALT, AST, and GGT percentiles. Age‐ and sex‐related reference intervals were established by using an LMS method of Cole–type method. Serum levels of transaminases follow age‐specific patterns and relate to the onset of puberty. This observation is more pronounced in girls than in boys. ALT percentiles showed similar‐shaped patterns in both sexes. Multivariate regression confirmed significant effects of puberty and BMI‐SDS (β = 2.21) on ALT. Surprisingly, AST serum levels were negatively influenced by age (β = −1.42) and BMI‐SDS (β = −0.15). GGT percentiles revealed significant sex‐specific differences, correlated positively with age (β = 0.37) and showed significant association with BMI‐SDS (β = 1.16). Conclusion: Current reference values of ALT, AST, and GGT serum levels were calculated for children between 11 months and 16.0 years, using modern analytical and statistical methods. This study extends the current knowledge about transaminases by revealing influences of age, sex, BMI, and puberty on serum concentrations of all three parameters and has for these parameters one of the largest sample sizes published so far. (Hepatology 2017).